Pengaruh Model Inkuiri Terbimbing Berbantuan Video Youtube Terhadap Pengetahuan Faktual, Konseptual, dan Prosedural IPA Siswa Kelas V - Titin Darneli; Irwan Koto; Agus Susanta (Universitas Bengkulu, 2023)
This study aims to detemine the effect of the guided incur learning model assisted by YouTube videos on factual, conceptual and procedural knowledge of students’ science in Class V. This research is a quantitative study. The method used quasy experiment. The design in this study Non-Equivalent control Group Design. The population in this study were all grade V students in the Madrasah Ibtidayah Darussalam Bengkulu City. The sample in this study is the VA Class of 22 students the experimental class, and the VB Class of 22 people as the control Class. The instrument used in the from of a written test consisted of dimensions of factual, conceptual and produral knowledge consisting of 20 multiple choice questions and 5 descripsion questions. The research data used inferential analysis of one-way Anova with the help of SPSS 20. The results showed that there was an influence of YouTube’s guided inquiry model in science learning on material change in material form on the factual,conceptual and procedural know ledge of science students in fifth grade MI.